2010
DOI: 10.1186/1746-1340-18-20
|View full text |Cite
|
Sign up to set email alerts
|

Relative effectiveness and adverse effects of cervical manipulation, mobilisation and the activator instrument in patients with sub-acute non-specific neck pain: results from a stopped randomised trial

Abstract: BackgroundNeck pain of a mechanical nature is a common complaint seen by practitioners of manual medicine, who use a multitude of methods to treat the condition. It is not known, however, if any of these methods are superior in treatment effectiveness. This trial was stopped due to poor recruitment. The purposes of this report are (1) to describe the trial protocol, (2) to report on the data obtained from subjects who completed the study, (3) to discuss the problems we encountered in conducting this study.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 86 publications
0
30
0
1
Order By: Relevance
“…23 The device used by Sobador A provided torsion pressure to facilitate the manipulative process; such devices are used by conventional manual therapy practitioners. 24 Marking a patient is also a manual therapy practice to help focus the treatment. 25 Sobador C used poultices; although the poultice techniques are traditional, Lewit mentions it as a substitute for electric muscle stimulation in conventional manual therapy.…”
Section: Discussionmentioning
confidence: 99%
“…23 The device used by Sobador A provided torsion pressure to facilitate the manipulative process; such devices are used by conventional manual therapy practitioners. 24 Marking a patient is also a manual therapy practice to help focus the treatment. 25 Sobador C used poultices; although the poultice techniques are traditional, Lewit mentions it as a substitute for electric muscle stimulation in conventional manual therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have also found minor AEs after patients undergoing a trial of SMT [7-12]. Some studies have looked at cervical SMT and the relationship of this care to AEs and clinical outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Effectiveness of manipulation and/or mobilization in isolation for acute or chronic non-speci ic neck pain remains inconclusive [42,44,45]. Our objective was to identify the independent and unilateral Mulligan clinical effect as a monotherapy, without any simultaneously conservative method.…”
Section: Discussionmentioning
confidence: 99%